2015
DOI: 10.1039/c5ta00199d
|View full text |Cite
|
Sign up to set email alerts
|

Direct growth of FePO4/reduced graphene oxide nanosheet composites for the sodium-ion battery

Abstract: The direct growth of FePO4/reduced graphene oxide nanosheet composite cathode material for sodium-ion batteries via a micro-emulsion technique, which exhibits excellent electrochemical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 50 publications
1
39
1
Order By: Relevance
“…We recorded the electrochemical impedance spectra for all four samples mentioned above (Figure 4b), and their Nyquist plots were different from each other, especially regarding the radius of the semicircle in the high-to-medium frequency range, which was related to the charge transfer and surface film resistance (R ct ) during the cation interfacial transfer between the electrode material and the electrolyte. 14 The fitting result of the electrochemical impedance spectroscopy test showed that R ct decreased as the FePO 4 thickness decreased (Supplementary Table S2). Not surprisingly, an increase in the thickness of the surface coating layer made the charge transfer on the interface harder due to the poor electronic conductivity of the amorphous FePO 4 shell, which was expected to induce a higher polarization for thicker layers and produced inferior electrochemical performance compared with the thinner layers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recorded the electrochemical impedance spectra for all four samples mentioned above (Figure 4b), and their Nyquist plots were different from each other, especially regarding the radius of the semicircle in the high-to-medium frequency range, which was related to the charge transfer and surface film resistance (R ct ) during the cation interfacial transfer between the electrode material and the electrolyte. 14 The fitting result of the electrochemical impedance spectroscopy test showed that R ct decreased as the FePO 4 thickness decreased (Supplementary Table S2). Not surprisingly, an increase in the thickness of the surface coating layer made the charge transfer on the interface harder due to the poor electronic conductivity of the amorphous FePO 4 shell, which was expected to induce a higher polarization for thicker layers and produced inferior electrochemical performance compared with the thinner layers.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the introduction of a highly conductive matrix to form a composite material becomes a logical and reasonable approach to achieve higher electron conductivity. [14][15][16][17][18] For example, Liu et al 10 showed that a mixture of single-walled carbon nanotubes and FePO 4 nanoparticles showed much improved battery performance and high cyclability. single-walled carbon nanotubes are a highly connected network that can facilitate the electron transport of embedded FePO 4 particles.…”
Section: Introductionmentioning
confidence: 99%
“…Na cycling properties of Na 3 V 2 (PO 4 ) 3 manifested a reversible capacity of 86 mA h g -1 at 5 C with polarization (0.15 V) , as opposite to only 43 mA h g -1 of bare NVP. Prominent electronic conductivity of 3.2 S cm −1 occurred in FePO 4 /graphene as cathode in SIBs,[213] which retained a reversible capacity of 112 mAh g -1 in 1 st cycle at 0.2 C and then stabilized at ~90 mAh g -1 ; more importantly, the cycle retention of ~60 mAh g −1 at 1 C and ~30 mAh g −1 at 4 C. Very recently, Liu et al[214] reported FePO 4 /rGO nanosheet by a microemulsion technique afforded 153.4 mAh g -1 after the 70th cycle at 0.1 C. As an interesting cathode material, graphene-based (NH 4 ) 0.19 V 2 O 5 ·0.44H 2 O composites, via a hydrothermal route followed by heat treatment by Fei et al,[215] delivered a discharge capacity of 141.5 mA h g -1 after 40 cycles at 20 mA g -1 in a 1.5-3.4 V voltage. In a recent literature,[216] the VO 2 arrays/graphene electrode delivered a Na storage capacity of 306 mAh Na-cycling at a long voltage plateau of 4.2 vs. Na + /Na.…”
mentioning
confidence: 94%
“…However, because high-temperature calcination will lead to the crystallization of amorphous FePO 4 , carbon decoration should be conducted at relatively low temperature. Various carbon matrixes have been introduced to improve the electrochemical properties of amorphous FePO 4 [97][98][99][100]. For example, Fang et al [101] reported a mesoporous amorphous FePO 4 embedded in carbon matrix, and the obtained FePO 4 /C electrode showed a high reversible capacity of 151 mAh g −1 with stable cycle life (Fig.…”
Section: Amorphous Phasesmentioning
confidence: 99%
“…6d) [124][125][126]. The tunnels are extended along the three main crystallographic directions [100], [010] and [001], giving a high Na + ionic conductivity (10 −6 S cm −1 ). Kang's group has investigated a series of Na 4 M 3 (PO 4 ) 2 (P 2 O 7 ) (M = Fe, Mn) materials [127][128][129], the Na 4 Fe 3 (PO 4 ) 2 (P 2 O 7 ) exhibited a reversible capacity of 129 mAh g −1 with a average potential of 3 V (Fig.…”
Section: A Ementioning
confidence: 99%